2014
DOI: 10.2304/pfie.2014.12.5.681
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Transition to Higher Education in Greece: Issues of Intergenerational Educational Mobility

Abstract: This article focuses on the study of intergenerational educational mobility in Greece. The primary purpose is to represent quantitatively the transitions of individuals, in order to determine whether and to what extent the educational levels attained are influenced by parental education. The authors use data drawn from the European Union Statistics on Income and Living Conditions and the ad hoc module on Intergenerational Transmission of Poverty (a supplement to the EU-SILC survey conducted on an annual basis)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Each element p ij (t), ∀i, j = 1, 2, 3 of the matrix P(t) describes the probability of an individual to move from state i (parental educational level) to state j (individual's educational level). The off-diagonal elements of the P(t) matrix signify the shifts or movements of individuals, while p ii indicates the probability of individuals remaining static over time in relation to their parental educational status (see also [15,16]). The above model describes a closed Non-Homogeneous Markov System, since our transition probabilities are estimated for each time step t. For a comprehensive description of the theoretical background of the Markov systems, see [29][30][31][32][33][34][35][36][37].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each element p ij (t), ∀i, j = 1, 2, 3 of the matrix P(t) describes the probability of an individual to move from state i (parental educational level) to state j (individual's educational level). The off-diagonal elements of the P(t) matrix signify the shifts or movements of individuals, while p ii indicates the probability of individuals remaining static over time in relation to their parental educational status (see also [15,16]). The above model describes a closed Non-Homogeneous Markov System, since our transition probabilities are estimated for each time step t. For a comprehensive description of the theoretical background of the Markov systems, see [29][30][31][32][33][34][35][36][37].…”
Section: Methodsmentioning
confidence: 99%
“…Blanden and Machin [14] investigate the relationship between education and intergenerational mobility, discussing the role of education in either facilitating or impeding social mobility. Moreover, Symeonaki and Stamatopoulou [15], Symeonaki et al [16], Stamatopoulou et al [17], and Stamatopoulou and Symeonaki [18] estimate intergenerational educational mobility across European countries, allowing for a comparative study of discrepancies among countries in social mobility, leveraging diverse large-scale European databases, while Symeonaki and Tsinaslanidou [19] studied intergenerational educational mobility across countries with different welfare regimes.…”
Section: Introductionmentioning
confidence: 99%
“…for families of a university-educated father and less so otherwise. The fact that access to higher education in Greece is easier for the socioeconomically privileged, raises issues of social justice and inequalities [9].…”
Section: Family Economic Sacrificementioning
confidence: 99%
“…The data seem to confirm Daouli, Demoussis and Giannakopoulos' research (2010) which found that there is substantial cross-generational educational mobility over time and that daughters seem to have a greater likelihood of upward transitions. Symeonaki and Stamatopoulou (2014) reveals that individuals' likelihood of attaining a higher educational level than that of their parents has increased in the last twenty years and that intergenerational cohort comparisons attest that upward mobility predominates over downward transitions and seems to increase over time, even though this increase has halted for the younger birth cohort.…”
Section: Introduction Three Variants Of Sociologically-oriented Educational Researchmentioning
confidence: 97%